Risk of Venous Thromboembolism in Statin Users Compared to Fibrate Users in the United Kingdom Clinical Practice Research Datalink (UK CPRD) GOLD - Ayodele O; Cabral HJ; McManus DD; Jick SS (Clinical Epidemiology, 2024)
Olulade Ayodele,1 Howard J Cabral,2,3 David D McManus,4 Susan S Jick1,5 1Department of Epidemiology, Boston University School of Public Health, Boston, MA, USA; 2Department of Biostatistics, Boston University School of Public Health, Boston, MA, USA; 3Biostatistics and Research Design Program, Boston University Clinical and Translational Science Institute, Boston, MA, USA; 4Department of Medicine, University of Massachusetts Medical School, Worcester, MA, USA; 5Boston Collaborative Drug Surveillance Program, Lexington, MA, USACorrespondence: Susan S Jick, Department of Epidemiology, Boston University School of Public Health, Boston, MA, USA, Tel +1 (781) 862-6660, Email sjick@bu.eduBackground: A substantial proportion of adults receive statins for treatment of hypercholesterolemia and cardiovascular risk, and statins have been found to improve outcomes in this patient population. However, studies have not consistently demonstrated the potential benefits of statins in preventing venous thromboembolism (VTE). Therefore, we conducted this study to investigate this association.Methods: We conducted a cohort analysis in a study sample comprised of 40– 79-year-old patients with hyperlipidemia who received at least one fibrate or statin prescription between January 1995 and December 2018 in the United Kingdom Clinical Practice Research Datalink (CPRD) GOLD. We evaluated the association between statin use and incident unprovoked VTE, compared to fibrate use, an active comparator, using Kaplan–Meier (KM) analysis, Poisson regression (with and without propensity score matching), and inverse probability of treatment weights (IPTW) marginal structural models (MSM).Results: In this cohort of 166,292 patients with hyperlipidemia, 0.81% (N=1,353) developed incident unprovoked VTE. In analyses using the KM method, patients who received statins had a slightly lower risk of VTE compared to those who received fibrates (Log rank test: p=0.0524). The adjusted incident rate ratio (95% CI) for VTE, calculated using Poisson regression, controlling for serum cholesterol and other baseline covariates, in patients prescribed statins compared to fibrates was 0.77 (0.45– 1.33) in the full cohort, 0.74 (0.38– 1.45) in the propensity score matched analysis, and 0.51 (95% conservative CI: 0.34– 0.76) in the IPTW MSM analysis.Conclusion: While the magnitude of effect varied across the different analytic methods, there is consistent evidence for a protective effect of statin use on the occurrence of unprovoked VTE.Keywords: hyperlipidemia, statin, fibrate, VTE